Assessment of genetic counselling and testing of patients diagnosed with invasive breast carcinoma in two South African breast units - Mukendi, Ilunga Valerien (University of the Witwatersrand, Johannesburg, 2023)
Genetic counselling and testing can be helpful and enable further management when a carrier is identified early. Mutations in BRCA 1/2 situated on chromosomes 17q21 and 13q12-13 are rare. BRCA 1/2 are tumour suppressor genes essential for preserving genomic integrity, and their mutations will lead to DNA repair deficiency and persistent impaired DNA replication. As a result, dysplasia and breast malignancy will occur. This study was conducted at Charlotte Maxexe Johannesburg Academic Hospital, the breast unit at Chris Hani Baragwanath Academic Hospital, the Division of Human Genetics at the National Health Laboratory Service and the University of the Witwatersrand. A total of 498 patients with breast cancer participated in the study. The study population was predominantly black (n=437; 87.75%), with 61 (12.25%) white patients. Most patients were in the 51-60 age group (n=134; 26.91%). There were 80 (16.06%) patients with a known family history of breast/ovarian cancer. Most patients (282; 56.63%) were not eligible for genetic counselling and testing. Of the 216 (43.37%) eligible patients, 39 (18.06%) received genetic counselling, 176 (81.4%) did not, and one (0.46%) refused counselling. All counselled patients received next-generation sequencing testing. Our findings show that next-generation sequencing is still underused in our health institutions. Most patients were not offered counselling despite meeting the criteria.
Research report It is being submitted in partial fulfillment for the degree of MMed to the Faculty of Health Science, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Genetic counselling and testing; Invasive breast cancer; BRCA; Charlotte Maxexe Johannesburg Academic Hospital; Chris Hani Baragwanath Academic Hospital; National Health Laboratory Service; Division of Human Genetics; Breast unit; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education